ANALISIS KETERAMPILAN MENULIS SISWA KELAS II PADA PEMBELAJARAN BAHASA INDONESIA DI SDN 112/I PERUMNAS - Vanni Sulastri Dewi Rumapea; Nuraini Kumala Suri; Septian Alya Hustria; Khoirunnisa (STKIP Subang, 2026)
This study aims to describe the writing abilities of second-grade elementary students and to identify factors influencing their development in Indonesian language learning. A qualitative approach was used, with data collected through interviews with a classroom teacher and a student. The results indicate that most students are able to write simple words and sentences, although their skills are still developing. Common challenges include distinguishing similar letters, writing longer words, and arranging sentences coherently. Environmental factors such as family support, peer interaction, and classroom atmosphere also play an important role in shaping students’ writing skills. The use of visual media and motivational strategies, including simple rewards, has been shown to increase students’ interest and engagement in writing activities. Furthermore, the teacher’s role is essential in guiding students and creating an active and enjoyable learning environment. Therefore, appropriate instructional strategies combined with supportive surroundings can effectively enhance students’ writing skills.